FRENCH SOFT POWER INSTRUMENTS AND MECHANISMS (Academia Science Repository, 2023)
This article talks about the concept of soft power, its role and importance in foreign policy, as well as the importance of soft power tools and mechanisms of France, which actively uses this concept in its foreign policy.